دور الأرغونوميا المهنية في تحسين جودة الأداء - بالي, عادل (University of Eloued جامعة الوادي, 2021)
ملخص الدراسة باللغة العربية ملخص الدراسة: هدفت هذه الدراسة إلى التعرف على دور الأورغونوميا في تحسين جودة الأداء الإداري، في مؤسسة اتصالات الجزائر – الوادي–. ولتحقيق أهداف الدراسة استعملنا المنهج الوصفي واعتمدنا على عدة أدوات لجمع المعلومات أهمها:مقابلات مع عمال داخل المؤسسة، كذلك على الملاحظةواستخدام استبيان مكون من 25سؤال موزعة على أربعين عامل لإثبات أو نفي فرضياتالدراسة. واعتمدنا على المسح الشامل لمجتمع البحث والمقدر بـ 40عاملا، وشمل التحليل الإحصائيللبيانات برنامج الحزمة الإحصائية للعلوم الاجتماعية ( SPSS)، التمثيلبالرسوم البیانیة وبناءاً على نتائج الدراسة التي توصلنا اليها من خلال نتائج التحليل الإحصائيلاستبيان الدراسة، توصلنا إلى الاستنتاجات التالیة: - إن لسوء التنسيق بين الإنسان والألة من خلال الوسائل المستعملة في مكان العمل دور في ضعف جودة الأداء في المؤسسة محل الدراسة. - إن غیاب القياسات الأنثربومتریة الجسمية في التصميم بأماكن العمل لها دور في حدوث بعض التأثيرات على صحة وسلامة العامل بمؤسسةاتصالات الجزائر- الوادي-. ومنه نستنتج تحقق فرضيتنا العامة أي أن : لتطبيق الأورغونوميا دور في تحسين جودة الأداء.   Summary This study aimed to identify the role of ergonomics in improving the quality of administrative performance, In Algeria Telecom - El-Wadi -. To achieve the objectives of the study, we used the descriptive approach and relied on several tools to collect information, the most important of which are: interviews with workers inside the institution, as well as on observation and the use of a questionnaire consisting of 25 questions distributed among forty workers to prove or negate the hypotheses of the study. We relied on the comprehensive survey of the research community estimated at 40 workers, and the statistical analysis of the data included the Statistical Package for Social Sciences (SPSS) program, represented by graphs, and based on the results of the study that we reached through the results of the statistical analysis of the study questionnaire, we reached the following conclusions: - The poor coordination between man and machine through the means used in the workplace has a role in the poor quality of performance in the institution under study. - The absence of anthropometric measurements in the design of workplaces has a role in the occurrence of some effects on the health and safety of the worker at Algiers Telecom - El Oued -. And from it we conclude that our general hypothesis is fulfilled, that is: The application of ergonomics has a role in improving the quality of performance.
دراسة ميدانية بمؤسسة اتصالات الجزائر - ولاية الوادي
مذكرة ماستر في علم الاجتماع تخصص تنظيم وعمل
Keywords: الأورغونوميا، تقييم الأداء، جودة الأداء; Orgonomie, évaluation des performances, qualité de la performance; Orgonomics, performance evaluation, quality of performance